Microcephaly, epilepsy, and neonatal diabetes due to compound heterozygous mutations in IER3IP1: insights into the natural history of a rare disorder. Issue 3 (21st October 2013) - Shalev, Stavit A; Tenenbaum‐Rakover, Yardena; Horovitz, Yoseph; Paz, Veronica P; Ye, Honggang; Carmody, David; Highland, Heather M; Boerwinkle, Eric; Hanis, Craig L; Muzny, Donna M; Gibbs, Richard A; Bell, Graeme I; et al.
Abstract Neonatal diabetes mellitus is known to have over 20 different monogenic causes. A syndrome of permanent neonatal diabetes along with primary microcephaly with simplified gyral pattern associated with severe infantile epileptic encephalopathy was recently described in two independent reports in which disease‐causing homozygous mutations were identified in the immediate early response‐3 interacting protein‐1 (IER3IP1) gene. We report here an affected male born to a non‐consanguineous couple who was noted to have insulin‐requiring permanent neonatal diabetes, microcephaly, and generalized seizures. He was also found to have cortical blindness, severe developmental delay and numerous dysmorphic features. He experienced a slow improvement but not abrogation of seizure frequency and severity on numerous anti‐epileptic agents. His clinical course was further complicated by recurrent respiratory tract infections and he died at 8 years of age. Whole exome sequencing was performed on DNA from the proband and parents. He was found to be a compound heterozygote with two different mutations in IER3IP1: p.Val21Gly (V21G) and a novel frameshift mutation p.Phe27fsSer*25. IER3IP1 is a highly conserved protein with marked expression in the cerebral cortex and in beta cells. This is the first reported case of compound heterozygous mutations within IER3IP1 resulting in neonatal diabetes. The triad of microcephaly, generalized seizures, and permanent neonatal diabetes should prompt screening for mutations in IER3IP1. As mutations in genes such as NEUROD1 and PTF1A could cause a similar phenotype, next‐generation sequencing approaches—such as exome sequencing reported here—may be an efficient means of uncovering a diagnosis in future cases.